The genus Waoraniella García Aldrete (Lachesillidae: Eolachesillinae: Waoraniellini) in Colombia: Two new species from the Andean region - Manchola, Oscar Fernando Saenz; Obando, Ranulfo González; Aldrete, Alfonso Neri García (Zootaxa, 2018)
Two species of Waoraniella from Valle del Cauca, represented by both sexes, are here described and illustrated. The new species were found in the Andean region, between 1000–2000 m above sea level, constituting the first record of the genus outside the Amazon Basin. An identification key and a distribution map of the known Waoraniella species is included.